Resisting Friendship in Shakespeare - Zamir, Tzachi (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2020)
Scholars have long sensed that Shakespeare distances himself from the ideology of perfect friendship, so dominant in his culture. This essay participates in this conversation by advancing two explanations for Shakespeare’s distrust of friendship. First, friends limit selves to what they were, preventing some transformations (examples discussed involve the love versus friendship tension played out in some of the comedies). Second, opening one’s heart to a friend requires abandoning self-love when recognizing the varied excellences which friends exhibit (a pattern of friendship resisted suggested by Timon of Athens). Keywords: Friendship, Narcissism, Timon of Athens, Resisting change, Self, Love